Tense, Aspect and Negation (TAN) in Ìgáṣí - Adéwálé Adéoyè, Jèlílì (Linguistik Online, 2019)
Studies that are available on Ìgás̩í have only classified the speech form as one of the speech forms under the Ako̩ko̩id language cluster but none has examined tense, aspect and negation in the speech form. The present study provides a descriptive account of tense, aspect and negation in the speech form. It maintains that tense in Ìgáṣí polarises future and non-future. It establishes, among other things, that the speech form uses the pre-verbal particle á to mark its future tense and demonstrates that aspects in the speech form are divided into perfect and imperfect. The study also claims that Ìgáṣí has three basic negative morphemes which are kpa, sẹ and àgẹ̀ and shows that the future tense, perfect and habitual aspects have overt morphemes that reflect their presence in negative sentences. It is further claimed that àgẹ̀ which is divisible into nominal prefix (à) and negator (gè̩) functions as the lexical negator in the speech form. Data in this study were obtained from native speakers of Ìgás̩í through oral interviews and their responses were recorded. It is hoped that this study, throws more light on the relationship among the functional categories (tense, aspect and negation) in Ìgás̩í speech form and document its syntax for posterity as nothing has been in that category.